Utilization of Eight Antenatal Care Contacts among Healthcare Providers in Central Gondar Zone, Northwest Ethiopia: A Cross-Sectional Study - Agerie Zeleke (Mashhad University of Medical Sciences, 2024)
Background & aim: Ensuring optimal maternal outcomes depends on adequate antenatal care. The World Health Organization recommends eight antenatal care contacts, but there is little evidence on their uptake. This study assesses the utilization and determinants of eight antenatal care contacts among health care providers in the Central Gondar Zone.Methods: A multicenter cross-sectional study was conducted from May to June,  2022 involving 421 health care providers in public health facilities who were randomly selected. Data were collected through face-to-face interviews and observations with a structured questionnaire. Epi-data version 4.6 and SPSS 23 facilitated data entry and analysis. Bivariable and multivariable logistic regressions were performed, reporting adjusted odds ratios (AOR) with a 95% confidence interval (CI).  Results: Of the 421 healthcare providers, only 20.9% used eight contacts for antenatal care. Significant determinants included workplace (AOR=8.29; 95% CI: 1.47-1.54), understanding the importance of eight contacts in antenatal care (AOR=7.9; 95% CI: 3.70-16.89), knowledge of eight antenatal care contacts (AOR=2.90; 95% CI: 1.63-5.12), and the ability to distinguish between eight and four antenatal care visits (AOR=9.00; 95% CI: 3.70-21.91).Conclusion: The utilization of eight antenatal care contacts remains suboptimal. Strategic interventions to address the identified barriers are essential to improve service utilization in line with recommended guidelines.